2020
DOI: 10.1155/2020/1583647
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Macrophages in Rheumatoid Arthritis: The Past, Present, and Future

Abstract: The ontogeny of macrophages in most organs has already been established. Owing to the limited number and inaccessibility of synovial macrophages (SMs), the origin of SMs has not been fully elucidated. Previous studies suggested that SMs have two major origins, namely, tissue-resident and monocyte-derived SMs. However, no systematic analysis to identify SM ontology in either physiological or pathological conditions has been available to date. In this review, we summarize relevant studies on the two main origins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Besides producing inflammatory cytokines and chemokines, monocytes/macrophages also play a role in adaptive immune system, which involves the pathogenesis of RA (13). In RA synovium, CD14 + cells co-locate with CD4 + T cells, indicating that monocytes/macrophages and T cells may crosstalk in vivo in an inflammatory environment (17).…”
Section: Macrophages Promote the Hyper-activation Of T Cells In Ramentioning
confidence: 99%
See 1 more Smart Citation
“…Besides producing inflammatory cytokines and chemokines, monocytes/macrophages also play a role in adaptive immune system, which involves the pathogenesis of RA (13). In RA synovium, CD14 + cells co-locate with CD4 + T cells, indicating that monocytes/macrophages and T cells may crosstalk in vivo in an inflammatory environment (17).…”
Section: Macrophages Promote the Hyper-activation Of T Cells In Ramentioning
confidence: 99%
“…The ratio of inflammatory(M1) and antiinflammatory(M2) macrophages is impaired in RA (9). CD14 + Bone marrow (BM) monocytes/macrophages are present in the joint synovium of RA patients, and they produce co-stimulatory molecules and inflammatory cytokines, and present an active phenotype (12,13). In RA synovial fluid, the frequency of CD14 + +/bright CD16 + monocyte population increase compared to that of healthy controls (14).…”
Section: Introductionmentioning
confidence: 99%
“…Synovial tissue macrophages were previously identified by highly expressing CD68 and CD163 (50). From these populations, lining synovial macrophages were discriminated from sub-lining cells by their expression of FcgRIIIa suggesting that macrophages in the lining layer play an important role in cellular clearance (51,52).…”
Section: Role Of Tissue Resident Synovial Cells In Joint Homeostasismentioning
confidence: 99%
“…In RA, the respective functions of the distinct macrophage subsets have now been well explored, and macrophages originating from recruited monocytes appear to have overall disease-promoting functions ( 150 , 151 ). Similarly, the majority of studies on OA-affected joints have identified inflammatory, monocyte-derived macrophages as the main culprit in promoting and sustaining inflammation ( 124 , 152 ).…”
Section: Monocyte and Macrophage Functions In The Injured And Osteo-arthritic Jointmentioning
confidence: 99%